Association between metabolic syndrome and mortality in patients with COVID-19: A nationwide cohort study. Issue 6 (November 2022) - Park, Hyo Jin; Jung, Jin-Hyung; Han, Kyungdo; Shin, Jean; Lee, Yoojeong; Chang, Yujin; Park, Kyeyeung; Cho, Yoon Jeong; Choi, Youn Seon; Kim, Seon Mee; Nam, Ga Eun
Abstract: Objectives: We investigated the association between metabolic syndrome (MetS) and mortality among coronavirus disease 2019 (COVID-19) patients in Korea. Methods: We analyzed 3876 individuals aged ≥ 20 years who were confirmed with COVID-19 from January 1 to June 4, 2020 based on the Korea National Health Insurance Service (NHIS)-COVID-19 database and had undergone health examination by NHIS between 2015 and 2017. Multivariable Cox proportional hazard regression analyses were performed. Results: Of total participants, the prevalence of MetS was 21.0% (n = 815). During 58.6 days of mean follow-up, 3.1 % (n = 120) of the participants died. Compared to individuals without MetS, COVID-19 patients with MetS had a significantly increased mortality risk after adjusting for confounders in total participants (hazard ratio [HR]: 1.68, 95 % confidence interval [CI]: 1.14–2.47) and women (HR: 2.41, 95 % CI: 1.17–4.96). A low high-density lipoprotein cholesterol level in total participants (HR: 1.63, 95 % CI: 1.12–2.37) and hyperglycemia in women (HR: 1.97, 95 % CI: 1.01–3.84) was associated with higher mortality risk. The mortality risk increased as the number of MetS components increased among total participants and women (P for trend = 0.009 and 0.016, respectively). In addition, MetS groups had higher mortality risk in aged ≥ 60 years (HR: 1.60, 95 % CI: 1.07–2.39), and never-smokers (2.08, 1.21–3.59). Conclusions: The presence of MetS and greater number of its components were associated with increased mortality risks particularly in female patients with COVID-19. Managing MetS may contribute to better outcomes of COVID-19.